PEMBAHARUAN HUKUM DAN RASA KEADILAN MASYARAKAT YANG RELIGIUS: PENGATURAN TINDAK PIDANA ZINA DALAM KUHP TERBARU - Ika Oktaviani Oktaviani; Agusmidah Agusmidah (Universitas Dharmawangsa, 2023)
ABSTRACTFundamental changes to the elements of criminal acts in the newest KUHP still leavepolemics in society. Article 411 KUHP prohibits sexual intercourse between partnerswithout ties. However, this article is an absolute complaint offense that can only besubject to an element of criminal offense when there is a complaint by a husband orwife who is bound by marriage and parents or children who are not yet married. Thepaper examines changes to the rules for zina in the newest KUHP to create a sense ofjustice in religious communities. The result of the study concluded that this zina articleclashes with religious and moral values, so that changes in the regulation of zina in thenewest KUHP are considered not to reflect the spirit of nation-minded society and havenot fulfilled the sense of justice of religious communities. Therefore, it is necessary toreview the changes in the regulation of zina in the newest KUHP so that they reflect thereligious and moral values that live in society.Keywords : Legal Reform, Sense of Justice, Crime of Zina, The Newest KUHP